ANALYTICAL MODEL AND CALCULATIONS OF THE AERODYNAMIC RETAINER OF CUT DETAILS FROM TEXTILE FROM THE STACK OF SEWING MACHINE LOADING MANIPULATORS - MISIATS МICHAEL; ORLOVSKY, BRONISLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper presents the results of the development and construction of a mathematical model for the design of an aerodynamic grabber of cut textile parts from a pile of loading manipulators of general-purpose sewing machines to create purpose-built robotic technological complexes based on them. Automatic one-by-one loading of cut parts from textile materials from a stack of sewing machines is one of the main stages of automation of the equipment and work process when using modern general-purpose computerized sewing machines. A numerical calculation of the stationary suction force F_st was performed during the piece-by-piece separation of cut textile parts from the stack by an aerodynamic gripper. It was established that the obtained results of the calculation of the stationary suction force of the gripper of the sewing manipulator can be used for other fairly close values of the geometric parameters of the aerodynamic plate. This allows us to assume that the equations used to calculate F_st reliably describe the studied work process under the accepted limitations and idealization of the work environment for piece-by-piece separation of cut textile parts from the foot. A mathematical model of an aerodynamic grabber of cut textile parts from a stack for automated loading of sewing machines has been developed. A method of calculating the stationary suction force of the aerodynamic grabber of the sewing manipulator based on the results of calculations based on the use of a mathematical model has been developed, which allows us to assume that the equations used to calculate F_st reliably describe the studied work process under the accepted limitations and idealization of the working environment for piece-by-piece separation of textile cut parts from the foot